1994
DOI: 10.1523/jneurosci.14-09-05325.1994
|View full text |Cite
|
Sign up to set email alerts
|

Changes in paired-pulse facilitation suggest presynaptic involvement in long-term potentiation

Abstract: Long-term potentiation (LTP) is a use-dependent form of synaptic plasticity that is of great interest as a potential cellular substrate underlying memory. It is important to determine the pre- and/or postsynaptic locus of LTP expression in order to study its underlying mechanisms. Despite intensive investigation, however, its locus of expression remains uncertain. It has been hypothesized that if LTP expression includes a presynaptic locus then it may alter the expression of another presynaptically mediated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
256
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(282 citation statements)
references
References 46 publications
(56 reference statements)
25
256
1
Order By: Relevance
“…It was previously shown that average PPF does not change with LTP, but PPF in individual slices does change (22), and the changes correlate with the magnitude of LTP induced (23). These results were confirmed recently (20,21).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…It was previously shown that average PPF does not change with LTP, but PPF in individual slices does change (22), and the changes correlate with the magnitude of LTP induced (23). These results were confirmed recently (20,21).…”
Section: Discussionsupporting
confidence: 67%
“…Baseline p was greater in group 2 because of testing in the high-calcium saline. The 3-fold increase in calcium produces a 7.4-fold increase in pEPSP size elicited by the same stimulus intensity (22). And baseline p was less in group 3 because of adding -CgTX.…”
Section: Ltp Magnitude Correlates With Initial Pmentioning
confidence: 86%
See 2 more Smart Citations
“…In control conditions, this protocol elicits a condition of Paired Pulse Facilitation (PPF), in which the amplitude of the FP elicited by the second stimulus (R2) is greater than the amplitude elicited by the first stimulus (R1). The degree of PPF is quantified by the R2/R1 ratio and a modification of this ratio is an indication of a presynaptic action on neurotransmitter release (Manabe et al, 1993;Schulz et al, 1994;Calabresi et al, 1997).…”
Section: Electrophysiological Experiments 221 Extracellular Recordmentioning
confidence: 99%